If a²+b² ∝ ab, prove that (a+b) ∝ (a-b)
Please do it in a easy method.
Answers
Answered by
14
Given, a² + b² ∝ ab
Or, a² + b² = k. ab [Where, k is a non zero variation constant]
Or,![\frac{ {a}^{2} + {b}^{2} }{ab} = \: k \frac{ {a}^{2} + {b}^{2} }{ab} = \: k](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+%7D%7Bab%7D+%3D+%5C%3A+k)
Or,![\frac{ {a}^{2} + \: {b}^{2} }{2 \: ab} = \frac{k}{2} \frac{ {a}^{2} + \: {b}^{2} }{2 \: ab} = \frac{k}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+%2B+%5C%3A+%7Bb%7D%5E%7B2%7D+%7D%7B2+%5C%3A+ab%7D+%3D+%5Cfrac%7Bk%7D%7B2%7D+)
By using componendo and dividendo, we can say :
![\frac{ {a}^{2} + \: {b}^{2} + 2ab}{ {a}^{2} + {b}^{2} - 2ab} \: = \frac{k + 2}{k - 2} \frac{ {a}^{2} + \: {b}^{2} + 2ab}{ {a}^{2} + {b}^{2} - 2ab} \: = \frac{k + 2}{k - 2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+%2B+%5C%3A+%7Bb%7D%5E%7B2%7D+%2B+2ab%7D%7B+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+-+2ab%7D+%5C%3A+%3D+%5Cfrac%7Bk+%2B+2%7D%7Bk+-+2%7D+)
Or,![\frac{(a + b)^{2} }{ ({a - b)}^{2} } = m \: \frac{(a + b)^{2} }{ ({a - b)}^{2} } = m \:](https://tex.z-dn.net/?f=+%5Cfrac%7B%28a+%2B+b%29%5E%7B2%7D+%7D%7B+%28%7Ba+-+b%29%7D%5E%7B2%7D+%7D+%3D+m+%5C%3A+)
In the above procedure, m is a constant equals to (k+2)/(k-2).
So, (a+b) = √m (a-b)
Or, (a+b) ∝ (a-b) [Since, √m is a non-zero variarion constant]
Hence, (a+b) ∝ (a-b) [PROVED]
Or, a² + b² = k. ab [Where, k is a non zero variation constant]
Or,
Or,
By using componendo and dividendo, we can say :
Or,
In the above procedure, m is a constant equals to (k+2)/(k-2).
So, (a+b) = √m (a-b)
Or, (a+b) ∝ (a-b) [Since, √m is a non-zero variarion constant]
Hence, (a+b) ∝ (a-b) [PROVED]
saif99:
hi
Answered by
0
Answer:
Step-by-step explanation:
Similar questions